Adverse drug events: description of an active search process in a teaching hospital of the Sentinela Network - Wanessa S. NOGUEIRA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To describe the implementation of an active search service for adverse drug events (ADE) in a teaching hospital in the Midwest region of Brazil. Method: Observational sectional study conducted at the Pharmacovigilance Service in a University hospital in the Midwest Region of Brazil, from March to August/2019. All patients admitted to a medical clinic unit were included and those who did not find medical records were excluded. A work process structured in six stages was elaborated: 1) elaboration of a list of triggers through literature review; 2) elaboration of a list of patients whose previously selected triggers appeared; 3) visiting the wards and reviewing medical records; 4) validation of ADE; 5) notification of ADE to Agência Nacional de Vigilância Sanitária; 6) registration of information in databases. Results: The Positive Predictive Value (PPV) of each tracker was calculated individually and globally. The relative and absolute frequency of ADE was calculated as to the type, description and the drug involved. A total of 479 searches were made in the period and the frequency of ADE was 7.48%. The global triggers PPV was 0.04. The trigger with the best performance was promethazine (1.00), followed by the Activated Partial Thromboplastin Time (0.67). Regarding the identified ADE, it was observed that most of the time, 24.14% were related to infusion reactions. It was observed that 53.85% of the drugs involved in ADE were high alert medications. Conclusion: It was observed that the implementation of an active search service for ADE in hospitals that do not have the support of an electronic medical record system is feasible to be performed. It was also observed a high frequency of ADE and that the active search guided by triggers allows to identify events that otherwise could not be identified.